The Effect of Competency and Work Motivation on Employee Performance at PT. Indomarco Prismatama Lebak Bulus, South Jakarta - Habibah, Ummi; Hermawati, Rahmi (STEBIS Bina Mandiri, 2025)
This study aims to determine how much influence the competence and work motivation have on the performance of employees of PT. Indomarco Prismatama Lebak Bulus, South Jakarta, both partially and simultaneously. This study uses a quantitative approach with a saturated sampling technique to 52 respondents. Data analysis was carried out through validity tests, reliability, multiple linear regression, T test, F test, and coefficient of determination (R²). The results of the study indicate that partially, the competence variable (X1) has a partial effect on the employee performance variable (Y) which can be seen from the t count> t table (19.589> 2.010) and the constant significance is smaller than 0.05 (0.000 <0.05). Likewise, the motivation variable (X2) also has a partial effect on the employee performance variable (Y) with t count> t table (4.772> 2.010) and the constant significance is smaller than 0.05 (0.000 <0.05). Simultaneously, the competency (X1) and motivation (X2) variables influence employee performance (Y) as seen in the Fcount value > Ftable (11,038 > 3.180) and the significance level is smaller than 0.05 (0.000 < 0.05). The Determination Coefficient is 0.340, which means that the influence of the independent variables, namely the Training and Competence variables, influences the dependent variable, employee performance by 34%, while the remaining (100-34%) = 66% is influenced by other variables.